Shear bond strength of precoated orthodontic brackets: an in vivo study - Ali H Hassan (Dove Medical Press, 2010)
Ali H HassanDepartment of Preventive Dental Sciences, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi ArabiaObjective: To evaluate the shear bond strength of precoated orthodontic brackets bonded with self-etching primer relative to that of noncoated conventionally-bonded brackets at two different time intervals.Methods: Twenty-one subjects were selected for randomized split-mouth bonding of two types of brackets to the maxillary arch. Half of the teeth had precoated brackets bonded using selfetching adhesive, and the other half had regular brackets bonded using Transbond XT adhesive. Nitinol wires were tied to the upper arch and were left until the time of debonding. The patients were randomly divided into two groups: one debonded after one hour and the other debonded two weeks after the initial wire placement. The shear bond strength was directly recorded from the patients’ mouths using an in vivo debonding device.Results: There were no significant differences in shear bond strength between the precoated and conventional groups or within each group at different time intervals. There were significant differences between anterior and posterior teeth in both the precoated and conventional groups. Conclusion: Pre-coated brackets bonded with self-etching adhesive have the same bonding strength as the conventionally bonded brackets.Keywords: shear bond, bonding, orthodontics, precoated, brackets, self-etching adhesive